Phylogenetic Diversity of T4-Type Phages in Sediments from the Subtropical Pearl River Estuary - He, Maoqiu; Cai, Lanlan; Zhang, Chuanlun; Jiao, Nianzhi; Zhang, Rui (Frontiers in Microbiology, 2017)
Viruses are an abundant and active component of marine sediments and play a significant role in microbial ecology and biogeochemical cycling at local and global scales. To obtain a better understanding of the ecological characteristics of the viriobenthos, the abundance and morphology of viruses and the diversity and community structure of T4-type phages were systematically investigated in the surface sediments of the subtropical Pearl River Estuary (PRE). Viral abundances ranged from 4.49 × 108 to 11.7 × 108 viruses/g and prokaryotic abundances ranged from 2.63 × 108 to 9.55 × 108 cells/g, and both decreased from freshwater to saltwater. Diverse viral morphotypes, including tailed, spherical, filamentous, and rod-shaped viruses, were observed using transmission electron microscopy. Analysis of the major capsid gene (g23) indicated that the sediment T4-type phages were highly diverse and, similar to the trend in viral abundances, their diversity decreased as the salinity increased. Phylogenetic analysis suggested that most of the g23 operational taxonomic units were affiliated with marine, paddy soil, and lake groups. The T4-type phage communities in freshwater and saltwater sediments showed obvious differences, which were related to changes in the Pearl River discharge. The results of this study demonstrated both allochthonous and autochthonous sources of the viral community in the PRE sediments and the movement of certain T4-type viral groups between the freshwater and saline water biomes.